Fractal analysis for OCT-A images of central serous chorioretinopathy - Arturo Carta; Angelique Donnio; Stefano Dore; Maurizio Fossarello; Roberta Farci (Photodiagnosis and Photodynamic Therapy)
Objective: to analyze OCT-A choriocapillary layer (CCL) images of patients affected by central serous chorioretinopathy (CSC) by means of fractal analysis. Design: a case-control study. Participants: 17 eyes of 16 patients affected by CSC were analyzed with OCT-A, and, successively, compared to 14 eyes of 8 healthy patients. Methods: OCT-A images were opened in Image J software (https://imagej.nih.gov/NIH, Bethesda, MD, USA). Skeletonization process was applied, and subsequently, a fractal analysis was performed. Thereafter, fractal analysis by means of FracLac plugin was also realized: multifractal tool was applied. Data were then imported into Excel spreadsheet for statistical analysis. An independent t-Test between cases and controls was performed. A Mann-Whitney test between cases and controls, and between fractal values and sex of the participants was also applied; Spearman test was realized between fractal variables and the age and the visual acuity, respectively. Results: mean fractal dimension (FD) of cases was 1,96±0,010; mean FD of controls was 1,86±0,02. Student t-test showed a significant difference between cases and controls (p=0,052). A statistically significant (p<0.05) correlation between visual acuity and mean FD (rho=0.519, p=0,033) was found. No significant correlation between age and the mean FD was found (p>0.519). No significant difference between males and females was found (p=0,245). Conclusions: fractal analysis is a new, alternative method to evaluate retinal imaging in CSC, which can make a new assessment of this retinal disease.